A Comparative Assessment of Nasal Appearance following Nasoalveolar Molding and Primary Surgical Repair for Treatment of Unilateral Cleft Lip and Palate. Issue 5 (November 2021) - Kurnik, Nicole M.; Calis, Mert; Sobol, Danielle L.; Kapadia, Hitesh; Mercan, Ezgi; Tse, Raymond W.
Abstract : Background: Although many cleft teams have adopted nasoalveolar molding to improve nasal form, few comparative studies have assessed the postoperative benefits of this treatment. Given that reported outcomes have been contradictory and that treatment involves considerable burden to families, the purpose of this study was to assess objective and subjective changes from nasoalveolar molding at approximately 5 years of age. Methods: All patients with complete unilateral cleft lip and palate who underwent primary cheiloplasty performed by a single surgeon over a 7-year period were reviewed. Patient results were grouped into nasoalveolar molding or no–nasoalveolar molding. Cleft severity and aesthetic outcomes were assessed by panels of raters who independently ranked subject images at presentation, immediately preoperative (after molding), and at 5-year follow-up. Objective symmetry was measured using standard anthropometric analysis on three-dimensional images. Results: Among 41 patients included, 16 successfully completed nasoalveolar molding. Both groups were similar at presentation; however, the nasoalveolar molding group had improved appearance following molding ( p < 0.05). After surgery, at 5 years of age, the nasoalveolar molding group had better rank scores for overall appearance ( p < 0.05), cleft nostril height, and cleft medial lip height ( p < 0.05). Regression analysis revealed that nasoalveolar molding treatment was the most significant predictor of overall nasal appearance at 5 years, but that treatment team experience and initial severity were also significant predictors ( p < 0.05). Qualitative audit following analysis identified favorable and unfavorable features of nasoalveolar molding. Conclusion: In children with complete unilateral cleft lip and palate, nasoalveolar molding was associated with better overall nasal aesthetics and improved cleft nostril height and cleft medial lip height at approximately 5 years of age. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.